2016
DOI: 10.1111/jgh.13260
|View full text |Cite
|
Sign up to set email alerts
|

CT differentiation of diffuse malignant peritoneal mesothelioma and peritoneal carcinomatosis

Abstract: Using a combination of CT findings may increase our ability to distinguish PC from DMPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Malignant peritoneal mesothelioma (MPeM) is a rare neoplasm arising from the serosal lining of the peritoneal cavity and is related to asbestos exposure in most cases [1]. Like pleural mesothelioma, it is quite aggressive, with most patients succumbing to this disease within 7-14 months after diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant peritoneal mesothelioma (MPeM) is a rare neoplasm arising from the serosal lining of the peritoneal cavity and is related to asbestos exposure in most cases [1]. Like pleural mesothelioma, it is quite aggressive, with most patients succumbing to this disease within 7-14 months after diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that gender, asbestos exposure, and histological subtype are associated with OS in MPeM [ 21 , 23 , 39 ]. However, in our study, none of above-mentioned factors was shown to be a predictor of MPeM.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that there was no significant difference in ascites LDH levels between patients with MPeM and those with PC, although the ascites-serum LDH ratio in patients with MPeM was higher. The reason for these findings might be that MPeM is originated from peritoneum; therefore, the peritoneum tumor burden is heavy with diffused and persistent infiltration [ 28 , 29 ], which is accompanied by more tissue injury induced by anaerobic glycolysis pathway and high ascites LDH levels. The major growth pattern of MPeM is peritoneal infiltration, and metastases are exceedingly rare, while the main growth pattern of PC is diffuse dissemination through the vasculature and lymph, which might account for higher serum LDH levels compared with patients with MPeM.…”
Section: Discussionmentioning
confidence: 99%